In Situ Synthesis of Zeolites in Solidified Fly Ash/Cement Matrices with High Na Content: Products, Pore Structure, and Leaching Behavior - Zhao Zheng; Zhitao Bao; Qingyi Wang; Yuxiang Li (Advances in Materials Science and Engineering)
Due to its high retention capacity and well durability, fly ash-based geopolymers rich of zeolites are considered to be potential solidified materials for low- and intermediate-level radioactive waste stream. This study mainly focused on the phase transformation, pore structure, and leaching characteristic of Sr2+ and Cs+ in solidified fly ash/cement matrices under different sodium hydroxide contents or sodium nitrate concentrations after thermal curing of 28 d. The results obtained from the experiments indicated that the geopolymers prepared from pure fly ash had the potential to transform into ordered structures at high temperatures of 90°C instead of room temperature, such as Na-P1 zeolite and chabazite. With the increase in sodium hydroxide contents, more sodium nitrate participated in the reaction to form a zeolite phase in solidified fly ash/cement matrices, while the coexistence phenomenon of chabazite and Na-P1 zeolite appeared under the condition of high sodium hydroxide contents of more than 5%. Just a proper number of zeolites can effectively inhibit the leaching of radionuclides Sr2+, as too many zeolites would lead to the increase in porosity, which was harmful to the retention of radionuclides. Solidified fly ash/cement matrices at a sodium hydroxide content of 5% or at a sodium nitrate concentration of 300 g/L obtained the lowest cumulative leaching fraction of Sr2+. Moreover, sodium hydroxide increased the cumulative leaching fraction of Cs+ which reversely decreased significantly with the increase in sodium nitrate concentrations.